Przez pryzmat wygnania. Zinaida Gippius o totalitaryzmie - Krycka-Michnowska, Iwona (Conversatoria Litteraria, 2021)
The views of Zinaida Hippius about Fascism, Nazism and Bolshevism presented in the pages of her diaries from the 30s and early 40s. are analysed in this article. The context for them is the writer's correspondence of this period. Particular attention was paid to the diarist’s perception of the dictators: Mussolini, Hitler and Stalin. Also the language and her style of expression was analysed. Zinaida Hippius regarded freedom as one of the highest value, so since the 1905 revolution she was opposed to various forms of tyranny and despotism. Analysis of the late writer's diaries and correspondence testifies to the fact that the embodiment of absolute evil from the October Revolution to the last moments of her life, in her opinion was Bolshevism. The writer considered Nazism as a creation and a homologous doctrine of Bolshevism.